Maternal and partner prenatal alcohol use and infant cognitive development - McCormack, C.; Hutchinson, D.; Burns, L.; Youssef, G.; Wilson, J.; Elliott, E.; Allsop, Steve; Najman, J.; Jacobs, S.; Rossen, L.; Olsson, C.; Mattick, R. (Elsevier Ireland Ltd, 2018)
Â© 2018 Elsevier B.V. Background: Teratogenicity of heavy prenatal alcohol exposure is established, but uncertainty remains regarding the impact of moderate alcohol exposure on cognitive deficits in infants. Separating in utero effects from environmental confounding is a challenge for observational studies; consideration of alcohol use by partners as well as mothers may help clarify this. This study examined associations between prenatal alcohol use by both mothers and their partners and infant cognitive developmental outcomes at 12-months. Methods: Pregnant women (n = 1331) and their partners (n = 699) were recruited from antenatal clinics of three metropolitan public hospitals in Australia, and completed detailed interviews about alcohol consumptions throughout pregnancy. Infants were assessed with the Bayley Scales of Infant Development âˆ’ Third edition (Bayley) at 12-months of age. Results: Alcohol use during pregnancy was reported by 65.7% of mothers and 84.1% of partners. Using multiple methods to adjust for confounding factors, no evidence for impaired cognitive ability associated with alcohol use by mothers or their partners was observed. Children born to women who drank low-levels of alcohol had slightly higher Bayley cognitive scores than those born to abstaining women. There was some evidence for an interaction between sociodemographic factors and prenatal alcohol exposure on infant cognitive outcomes. Conclusion: This finding corroborates existing evidence to suggest there are no detrimental effects to infant cognitive development at 12-months of age following low-level prenatal alcohol exposure. Future prospective studies involving families of a broad range of backgrounds would be informative to clarify interaction between alcohol exposure and environmental factors on developmental outcomes.